DAGUSIBU (OBTAIN, USE, STORE, AND DISPOSE): DRUG MANAGEMENT COUNCELLING FOR THE ELDERLY - Hilda Rohadatul Aliyah; Zahro Aisyi Khaddah; Yulia Retno Agustin; Azwar Mirza Al Fath; Putri Wulandari; Fransisca Dita Mayangsari (Journal of Community Research and Engagement, 2025)
Background: The lack of public awareness regarding proper medicine management contributes to irrational drug use and improper disposal, which can harm the environment, water sources, and ecosystems. Observations in Miru Village, Sekaran District, Lamongan Regency indicate that the community, particularly the elderly, has never received education on the principles of DAGUSIBU (Obtain, Use, Store, Dispose). Therefore, educating the public, especially the elderly, is essential to enhance their knowledge of safe and effective drug management. Objective: This initiative aims to improve the elderly’s understanding of how to obtain, use, store, and dispose of medicines properly. Method: Educational sessions were conducted using lectures, question-and-answer discussions, and visual aids including posters and brochures. These sessions took place at Pasadena Pharmacy, Miru. To assess the program’s effectiveness, participants completed pre-test and post-test assessments, along with satisfaction questionnaires. Results: Shows an increase in knowledge from pretest and posttest where the pretest results before the presentation of the material were only 20% then after the presentation of the material the posttest value increased to 95% until it reached 100%. In addition, the satisfaction of most participants expressed satisfaction with the presentation of the material that had been done. Conclusion: This community service program has proven to be effective in increasing public knowledge about DAGUSIBU. Improved understanding of proper medicine management can enhance public health and promote safer drug use, ultimately reducing the risks associated with improper medication practices.